Disease and treatment burden in patients with leukaemia: family members/partner perspective - Oliva, Esther Natalie; Ionova, Tatyana; Nier, Samantha; Pemberton-Whiteley, Zack; York, Nick; Costello, Denis; Salek, Sam (Frontiers in Hematology, 2025)
BackgroundLeukaemia patients require comprehensive care, including treatment, hospital visits, and family support. An awareness of the impact of leukaemia on family members is crucial. The Acute Leukemia Advocates Network, Chronic Lymphoid Leukemia (CLL) Advocates Network, and Chronic Myeloid Leukemia (CML) Advocates Network assessed the impact of leukaemia on patients and their families.MethodsA global anonymous online study ran from 18/09/21 to 07/01/2022, targeting leukaemia patients and their family members/partners. Demographic information, disease characteristics, treatment, and family members’ experience of caring for a relative with blood cancer were collected. Family members/partner assessed the disease impact on patients using the Hematological Malignancy-Patient Reported Outcome measure (HM-PRO) Part-A.Results571 family members/partners (70.9% female, aged 55 years) responded. They represented patients with CML (32.0%), CLL (26.3%), acute myeloid leukaemia (AML) (19.3%) acute lymphoblastic leukaemia (17.5%), and other leukaemias (4.9%). The majority (89.1%) lived with the patient, and 69.7% accompanied them to clinics. Daily support included household chores (60%), shopping (51.5%), transportation (37.1%), finances (28.9%), personal care (23.3%) and childcare (16.8%). About one-third (29.6%) felt that the diagnosis was insensitively conveyed and 81.3% sought prognosis information. Approximately 64% searched for alternative treatments. Approximately 40% of family members/partners (prevalently sons/daughters) expressed an impact on general quality of life, particularly on emotional behaviour and eating/drinking habits. The impact was greatest in family members representing patients aged <18 years with ALL and AML compared to CLL and CML.ConclusionThe burden on leukaemia patients’ family members is significant but often overlooked.